Anti-tumor necrosis factor-α therapy increases plaque burden in a mouse model of experimental atherosclerosis. (October 2018) - Oberoi, Raghav; Vlacil, Ann-Kathrin; Schuett, Jutta; Schösser, Florian; Schuett, Harald; Tietge, Uwe J.F.; Schieffer, Bernhard; Grote, Karsten
Abstract: Background and aims: Atherosclerosis is critically fueled by vascular inflammation through oxidized lipids and inflammatory cytokines such as tumor necrosis factor (TNF)-α. Genetic disruption of Tnf-α reduces atherosclerosis in experimental mouse models. However, less is known about the therapeutic potential of Tnf-α blockage by pharmacological inhibitors such as monoclonal antibodies, which are already approved for several inflammatory disorders in patients. Therefore, we investigated the effect of pharmacological TNF-α inhibition on plaque development in experimental atherosclerosis. Results: 10 week old male Ldlr −/− mice were divided into 4 groups (n = 7–10) and fed a high fat, high cholesterol diet for 6 and 12 weeks. Simultaneously, the mouse-specific anti-Tnf-α monoclonal antibody CNTO5048 (CNT) or a control IgG was administered. Results: CNT reduced circulating inflammatory markers without affecting body weight and glucose metabolism. Unexpectedly, CNT treatment increased plasma triglyceride levels and pro-atherogenic very-low-density lipoprotein (VLDL) cholesterol as well as plaque burden in the thoracoabdominal aorta and in the aortic root. In addition, we observed decreased smooth muscle cell content in the lesions and a trend towards reduced collagen deposition upon Tnf-α inhibition. Furthermore, inflammatory gene expression in the aortic arch was increased following Tnf-α inhibitor treatment. Conclusions: Although up to 12-week pharmacological inhibition of TNF-α in Ldlr −/− mice diminishes systemic inflammation, experimental plaque burden and vascular inflammatory gene expression are increased, while markers of plaque stability decrease. These observations may be explained by the development of a pro-atherogenic plasma lipid profile. Graphical abstract: Image 1 Highlights: The mouse-specific anti-TNF-α monoclonal antibody CNTO5048 (CNT) reduces circulating inflammatory markers in Ldlr-KO mice. However, CNT increases pro-atherosclerotic cholesterol levels as well as experimental plaque burden. In addition, CNT decreased smooth muscle cell content in the lesions and increased inflammatory aortic gene expression.